2016
DOI: 10.3389/fsurg.2016.00006
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Femoroacetabular Impingement in Core Muscle Injury/Athletic Pubalgia: Diagnosis and Management

Abstract: Chronic groin pain in athletes represents a major diagnostic and therapeutic challenge in sports medicine. Two recognized causes of inguinal pain in the young adult athlete are core muscle injury/athletic pubalgia (CMI/AP) and femoroacetabular impingement (FAI). CMI/AP and FAI were previously considered to be two distinct entities; however, recent studies have suggested both entities to frequently coincide in the athlete with groin pain. This article briefly discusses the role of FAI in CMI/AP and the diagnosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 18 publications
0
17
0
1
Order By: Relevance
“…Recently, some authors demonstrated the association between osteitis pubis/athletic pubalgia and femoroacetabular impingement (FAI) 44,45. In these patients, better results have been reported after treatment of both intra and extra-articular pathologies, with a high rate of return to previous level of activity/sport 46,47…”
Section: Treatment and Return To Sportmentioning
confidence: 99%
“…Recently, some authors demonstrated the association between osteitis pubis/athletic pubalgia and femoroacetabular impingement (FAI) 44,45. In these patients, better results have been reported after treatment of both intra and extra-articular pathologies, with a high rate of return to previous level of activity/sport 46,47…”
Section: Treatment and Return To Sportmentioning
confidence: 99%
“…Combined surgical treatment of concomitant hip and CMIs has been described 15,16 and is a safe and effective treatment in our experience (unpublished). Should these procedures be staged, there is no evidence that one should be performed before the other, and, in our experience, more than 2 weeks is not necessary between procedures.…”
Section: Operative Considerationsmentioning
confidence: 85%
“…These include the nonspecific symptoms and clinical findings during examination as well as the other potential causes of groin pain (such as FAI and associated acetabular labral tears) in athletes. 2 , 22 , 23 In many athletes, groin pain may be the result of a combination of findings, and the clinician must decipher the symptomatic pathology that requires surgical treatment. As a result, there is a lack of standardized diagnostic workup for a CMI.…”
Section: Discussionmentioning
confidence: 99%